Pengenalan Tumbuhan Lokal Untuk Kosmetik Kepada Gen Z : Edukasi Formulasi Sediaan Pomade Estrak Daun Meniran ((Phyllanthus Niruri L ) Sebagai Perangsang Penumbuh Rambut - Syafitri, Anggun; Rahmi, Sofia; Tamba, Agnes Clara; Hayati, Silmi (INSTITUT KESEHATAN DELI HUSADA, 2024)
Health Vocational High School is a place of education where students study. Busy student activities can sometimes reduce students' knowledge regarding the use of natural materials. The method applied in community service activities is providing counseling and education in the form of lectures and questions and answers directly by practicing making pomade cosmetics. Students' lack of knowledge regarding the use of natural ingredients from meniran leaves (Phyllanthus niruri L) as the main ingredient in natural pomade cosmetics which functions as a hair growth stimulant. For this reason, students are given education and understanding about the formulation of meniran leaf extract pomade preparations. The aim of holding service activities for students is